If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + 5x) = 7(x + 5) (1 * -7 + 5x * -7) = 7(x + 5) (-7 + -35x) = 7(x + 5) Reorder the terms: -7 + -35x = 7(5 + x) -7 + -35x = (5 * 7 + x * 7) -7 + -35x = (35 + 7x) Solving -7 + -35x = 35 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -7 + -35x + -7x = 35 + 7x + -7x Combine like terms: -35x + -7x = -42x -7 + -42x = 35 + 7x + -7x Combine like terms: 7x + -7x = 0 -7 + -42x = 35 + 0 -7 + -42x = 35 Add '7' to each side of the equation. -7 + 7 + -42x = 35 + 7 Combine like terms: -7 + 7 = 0 0 + -42x = 35 + 7 -42x = 35 + 7 Combine like terms: 35 + 7 = 42 -42x = 42 Divide each side by '-42'. x = -1 Simplifying x = -1
| 120/350 | | 5y^2+4+1y=4 | | 2m^3+2m^2-24m= | | f(x)=164-16x | | W-15=0 | | 3/7•14 | | 48+54r=-15r | | 6r-18=-32+4r | | -12/17y=13 | | -15x-8-(-25)+18x=0 | | 4.375=28/v | | 5x-20+16x+16=6x+6+5x+50 | | 3x+3=1/81 | | 260h+18=240h+22 | | 3z-19=-11+z | | 2+.5= | | 4x+80=-6x-8 | | sqrt(3x+12)+sqrt(3x-8)=10 | | sinx=sqrt3/2 | | 8d-32+24d-64=40 | | x^4-x^2+3=0 | | 2x-5whenx=12 | | -2x-1=-4 | | a/6=25 | | 24-12-(-14)=x | | P-8=12-3p | | 4p+1000000=12600000 | | ln(x+1)+ln(x+1)=2 | | g-9=-2g+6 | | -7/3/3/4 | | 10b+4=3B+16 | | .6x^2-18x-2=0 |